2014
DOI: 10.15171/jcvtr.2014.020
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Radiation Exposure in Coronary Angiography and Angioplasty: The Impact of Different Projections

Abstract: Introduction: We aimed to determine angiography projections with lower Dose Area Product (DAP) rate by measuring the mean DAP and fluoroscopy times in coronary angiography (CAG) and percutaneous coronary intervention (PCI) and calculating DAP rate in different projections. Methods: DAP and fluoroscopy times were measured in all employed projections in real-time in 75 patients who underwent CAG or PCI by a single cardiologist in Madani Cardiovascular University Hospital (45 in CAG group and 30 in PCI group). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
3
5
1
Order By: Relevance
“…This was due to longer fluoroscopy duration involved in engaging the catheter into the left and right system in addition to cine run. Similar finding has been reported by Farajollahi et al (24) using LAO40° compared to LAO40°‐CAU10° and LAO40°‐CRA10°. Contrary to our findings, it is reported that the maximum contribution of overall KAP during CA procedure was from RAO projection compared to LAO, LAT, and PA projections 25 , 26 .…”
Section: Discussionsupporting
confidence: 90%
“…This was due to longer fluoroscopy duration involved in engaging the catheter into the left and right system in addition to cine run. Similar finding has been reported by Farajollahi et al (24) using LAO40° compared to LAO40°‐CAU10° and LAO40°‐CRA10°. Contrary to our findings, it is reported that the maximum contribution of overall KAP during CA procedure was from RAO projection compared to LAO, LAT, and PA projections 25 , 26 .…”
Section: Discussionsupporting
confidence: 90%
“…Radiation dose and beam angulations contribute to the total amount of received radiation ( 3 5 ). As multiple projections may be used for optimal visualization of the coronary lesions, the amount of the radiation exposure during fluoroscopy and cine acquisition could vary with beam projection being a determining factor.…”
Section: Introductionmentioning
confidence: 99%
“…As the transradial approach is gaining more popularity ( 11 13 ), it is important to note that most of the studies focusing on the amount of radiation in various projections have been conducted via the transfemoral approach ( 3 , 4 ). There is only one study in the literature that has examined the radiation dose from different projections during coronary angiography via transradial approach ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that the total number of these procedures will increase several folds by 2020 with the development of new angiography systems and with an increase in skills necessary for carrying out complex coronary artery treatment procedures. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%